Enable contrast version

# Tutor profile: Purandhar B.

Inactive
Purandhar B.
Tutor Satisfaction Guarantee

## Questions

### Subject:Calculus

TutorMe
Question:

If f(x) is a differentiable function such that f '(0) = 2, f '(2) = -3 and f '(5) = 7 then the limit lim ( [f(x) - f(4)] / (x - 4) ) as x approaches 4 ?

Inactive
Purandhar B.

if we put 4 in place of x the we get 0/0 form so we need to differentiate numerator and denominator separately. => lim ( [f(x) - f(4)] / (x - 4) ) = lim ( [f ' (x) / 1) as f(x) - f(4) when differentiated we get f ' (x) as differentiation of constant is zero. Similarly differentiation of x - 4 is 1 as differentiation of x is 1 and constant is 0. lim ( [f(x) - f(4)] / (x - 4) ) as x approaches 4 = lim ( f ' (x) ) as x approaching 4 the answer is f ' (4) which cannot be found from the given information. so more information is needed.

### Subject:C Programming

TutorMe
Question:

What are the different ways of passing parameters to the functions? Which to use when?

Inactive
Purandhar B.

--Call by value We send only values to the function as parameters. We choose this if we do not want the actual parameters to be modified with formal parameters but just used. --Call by reference We send address of the actual parameters instead of values. We choose this if we do want the actual parameters to be modified with formal parameters.

### Subject:Algebra

TutorMe
Question:

If f(x) = 5 - (2^x), let g(x) be the inverse of function f(X). then g(-3) = ? ( '^' indicates power function)

Inactive
Purandhar B.

First we need to find g(x) from given f(x) and using inverse relation. y = 5 - 2^x , ****given and let f(x) be denoted by 'y'**** x = 5 - 2^y , ****interchange x and y in order to inverse of f(x) because inverse mean domain become co-domain and co-domain is domain.**** Solving for y now 2^y = 5 - x , ****apply log to the base two on both sides**** y = log(5-x), ***** here log base is 2***** now in place of y we can replace inverse of f(x) which is g(x) => g(x) = log (5 - x) ****(BASE 2)**** g(-3) = log( 5 - (-3) ) g(-3) = log(8) = log ( (2) ^ 3) ) *** 2 cube is 2^3 = 8***** g(-3) = 3 *** log (x^a) = a when base is x for the log***

## Contact tutor

Send a message explaining your
needs and PURANDHAR will reply soon.
ContactÂ PURANDHAR